The IL-12 cytokine family in cardiovascular diseases. (October 2019) - van der Heijden, T.; Bot, I.; Kuiper, J.
Highlights: The IL-12 cytokine family is a unique group of heterodimeric cytokines. The IL-12 cytokine family members and its receptors are expressed in atherosclerotic lesions. Increased serum levels of IL-12, IL-23 and IL-27, but reduced levels of IL-35, are associated with cardiovascular diseases. Abstract: Cytokines of the Interleukin (IL)-12 family, consisting of IL-12, IL-23, IL-27 and IL-35, are important regulators in (chronic) inflammatory disorders such as rheumatoid arthritis and multiple sclerosis, but also in cardiovascular diseases. Cytokines of the IL-12 family consist of two subunits and are known for their regulatory functions in the immunologic response, more specifically in the regulation and differentiation of T-helper (Th) cells such as Th1 and Th17 cells. Binding of these cytokines to its specific heterodimeric receptor results in the activation of the JAK-STAT signaling. Despite similarities in structure, the members of the IL-12 family have diverse, both pro- and anti-inflammatory, effects and functions. Because of the pro-inflammatory effects of IL-12 cytokine family members on immune responses, the IL-12 cytokines have been implicated in the development and progression of cardiovascular diseases such as atherosclerosis, but also in acute cardiovascular syndromes such as myocardial infarction and stroke. For example, patients suffering from cardiovascular disease display increased blood levels of IL-12, IL-23 and IL-27, while decreased IL-35 levels have been linked to a lower cardiovascular risk. In this review, we aim to highlight the current understandings of the IL-12 cytokine family and its specific family members to cardiovascular diseases, including both clinical and experimental studies. We will also discuss the potential of these cytokines as a biomarker in acute cardiovascular syndromes.